Speech coding : a computer laboratory textbook - Barnwell, T. P. 1943- (John Wiley and Sons, 1996)
This book contains: An overview of the issues in speech coding systems; The experimental environment used in the remainder of the book; The concepts and exercises associated with signal quantization; The differential coding using fixed linear predictors; A fully parametric vocoder in the form of a pitch-excited linear predictive coder; A synthesis of materials; An analysis-by-synthesis vocoders; and Frequency-domain coders.